Pesticide mixture toxicity to algae in agricultural streams – Field observations and laboratory studies with in situ samples and reconstituted water - Jenny Rydh Stenström; Jenny Kreuger; Willem Goedkoop (Ecotoxicology and Environmental Safety, 2021)
Long-term pesticide water concentrations were investigated in four agricultural streams and their mixture toxicity on algae was assessed, based on realistic (i.e. observed) concentrations in laboratory tests using (i) natural weekly water samples and (ii) reconstituted pesticide-spiked water samples representing mixtures with predicted high mixture. This approach both covered the full complexity of natural water samples and the controlled approach of reconstituted water samples. Long-term monitoring data (time-integrated, weekly samples) revealed more than 11 pesticides (range 11.0 ± 0.25–24.0 ± 0.44) in 75% or more of the almost 1600 samples collected between 2002 and 2018. ∑TUalgae exceeded 0.1 for 29 observations (or 1.8%). Despite the multitude of pesticides in a sample, ∑TUalgae was frequently set by one or a few dominating pesticides that contribute to more than 90% of the mixture’s toxicity. Algal growth inhibition tests with in situ stream water showed a high frequency of inhibition, despite the low ∑TU for most of these samples (range 0.000014–0.3858). These “false positive” results were attributed to confounding effects of turbidity, the complexation of nutrients, and toxic effects of metals and/or other unknown contaminants. Algal inhibition tests with spiked reconstituted water showed significant inhibitory effects in the range of 1–10x the ∑TUalgae observed in worst-case field samples. Although these tests disregard the chemical complexity of natural water, they show that inhibitory effects of pesticides on algae may occur at the ∑TUalgae observed in monitoring. Furthermore, considering that the ∑TUalgae of stream water are based on weekly average concentrations and likely underestimate short-term peak concentrations of pesticides, these results strongly suggest that inhibitory effects on algae may occur in the agricultural streams of southern Sweden. We conjecture, however, that the rapid recovery of algae contributes to ameliorate these short-term effects and that pesticide contamination should be seen as one of many stressors in the streams that drain agricultural landscapes.